Developing Early Reading Ability Of Early Childhood Through A Setting Of Letters Cards On Objects In Group B At TK Tunas Bawang, Lapandewa District, South Buton Regency - Asri Yani; Nadir La Djamudi; Siti Misra Susanti (Universitas Muhammadiyah Ponorogo, 2021)
This research aimed to develop early reading ability of early children through letter card games. This type of research is a type of classroom action research using Kurt Lewin's model including: planning, implementation, observation and reflection. This action was carried out in two cycles, each cycle in two meetings with the subject of 16 children in group B of Tunas Bawang Kindergarten. The object of research focused on developing children's early reading skills through letter card games. The data collection methods covered observation, interviews, and documentation. Data were analyzed by qualitative and quantitative descriptive techniques in the form of percentages of observations. The results showed that there was an increase in early reading ability which can be seen from 40% before the action. In the first cycle, it increased to 64.06% and in the second cycle, it increased by 90.95%. The improvement in early reading skills can be seen from the child being able to mention letter symbols, being able to name and grouping vowels and consonants, being able to name and grouping pictures, being able to combine letters into meaningful words, and being able to understand the meaning of pictures.